A Specific N=2 Supersymmetric Quantum Mechanical Model: Supervariable Approach - Aradhya Shukla (Advances in High Energy Physics)
By exploiting the supersymmetric invariant restrictions on the chiral and antichiral supervariables, we derive the off-shell nilpotent symmetry transformations for a specific (0 + 1)-dimensional N=2 supersymmetric quantum mechanical model which is considered on a (1, 2)-dimensional supermanifold (parametrized by a bosonic variable t and a pair of Grassmannian variables (θ,θ¯)). We also provide the geometrical meaning to the symmetry transformations. Finally, we show that this specific N=2 SUSY quantum mechanical model is a model for Hodge theory.